Levantamiento del patrimonio gastronómico en las fiestas de la Mama Negra Latacunga, Cotopaxi, Ecuador - Remache García, Andrea Juliana (2024)
The Mama Negra Festivities are a traditional celebration that combines religious, cultural, and folkloric elements, paying homage to the Virgin of Mercy and the Mama Negra, a figure representing the fusion of indigenous, African, and Spanish cultures, declared Cultural Heritage of Ecuador since 2005. This festivity, held in September and November, includes a diverse gastronomic heritage with dishes such as hornado, roasted guinea pig, tamales, chugchucaras empanadas, and more. However, the festival faces various challenges threatening its authenticity and valuation. One of the main problems is the loss of identity, flavor, and authenticity of local cuisine due to modifications of traditional recipes and their substitution by modern versions, negatively affecting the gastronomic experience during celebrations. Furthermore, the sustainability of key ingredients is at risk due to biodiversity loss, environmental deterioration, and lack of attention in the agricultural area, compromising the future availability of essential ingredients. Another problematic factor is the displacement of local traditional food vendors by fast food chains, devaluing local gastronomy, affecting the economy, and reducing the authenticity of dishes served during festivities. This research is based on a basic investigation with a mixed approach. The methods used were inductive-deductive, helping to collect information focused on gastronomic heritage\; furthermore, the analytical-synthetic method was used. In conclusion, the historical method was also used to reflect on the changes that gastronomy has brought since its inception and the influence it has had. The research was carried out in the city of Latacunga, where gastronomic establishments offering representative cuisine of this festival were identified and consumed throughout the year.